دور التمكين الإداري في تحقيق التميز بالمركبات الرياضيةدراسة ميدانية للمركب الرياضي الجواري روابحي رابح بحمام الضلعة - رحماني، عبد العزيز; Supervisor :قروش، النواري (Mohamed Boudiaf University of M'sila, 2024)
الملخص : تهدف هذه الدراسة إلى التعريف بموضوع دور التمكين الإداري في تحقيق التميز في المركبات الرياضية مع دراسة حالة المركب الرياضي الجواري روابحي رابح بحمام الضلعة زمنه تم تقسيم الدراسة إلى 3 جوانب، جانب منهجي وجانب نظري وجانب تطبيقي، إضافة إلى استخدام الاستبيان كأداة رئيسية في جمع البانات والمعلومات والتي تم تحليلها بالاعتماد على برنامج الحزمة الإحصائية spss وكذلك اعتمدت الدراسة على المنهج الوصفي التحليلي، وقد توصلنا إلى مجموعة من النتائج أهمها: إثبات أن للاتصال ومشاركة المعلومات دور في تحقيق التميز بالمركبات الرياضية.. إثبات أن للثقة بين العاملين والمسؤولين دور في تحقيق التميز بالمركبات الرياضية.. إثبات أن للحوافز المادية والمعنوية دور في تحقيق التميز بالمركبات الرياضية. عنوان الدراسة : دور التمكين الإداري في تحقيق التميز بالمركبات الرياضية دراسة ميدانية للمركب الرياضي الجواري روابحي رابح بحمام الضلعة  أهداف الدراسة : بمفهوم التمكين الإداري ومكوناته وأهميته ومفهوم أداء العاملين في المركبات الرياضية من  خلال الإطار النظري.  *إبراز دور تطبيق سياسة التمكين الإداري في تحقيق التميز في المركبات الرياضية.  *التعرف على العناصر الأساسية للتمكين الإداري (الاتصال ومشاركة المعلومات والثقة بين العاملين  والمسؤولين والحوافز المادية والمعنوية) ودورها في تحقيق التميز داخل المركبات الرياضية.  *إمكانية الوصول إلى استنتاجات من خلال تحليل إجابة عينة الدراسة وأهمية تطبيق التمكين الإداري  كممارسة إدارية ودورها الإيجابي في الوصول لأحسن أداء لدى العاملين في المؤسسات الرياضية.  *تقديم بعض المقترحات والتوصيات في ضوء النتائج التي تتوصل إليها الدراسة للاستفادة منها في تعميم  هذه النتائج والأخذ بالمقترحات والتوصيات.  التساؤل العام الدراسة : هل للتمكين الإداري دور في تحقيق التميز بالمركبات الرياضية؟ التساؤلات الجزئية : هل للاتصال ومشاركة المعلومات دور في تحقيق التميز في المركبات الرياضية؟ هل الثقة بين العاملين والمسؤولين دور في تحقيق التميز في المركبات الرياضية؟ هل للتحفيز المادي والمعنوي دور في تحقيق في المركبات الرياضية؟ الفرضية العامة للدراسة : *للتمكين الإداري دور في تحقيق التميز بالمركبات الرياضية  الفرضيات الجزئية: *للاتصال ومشاركة المعلومات دور في تحقيق التميز بالمركبات الرياضية.  *للثقة بين العاملين والمسؤولين دور في تحقيق التميز بالمركبات الرياضية.  *للتحفيز المادي والمعنوي دور في تحقيق التميز بالمركبات الرياضية. المنهج المتبع في الدراسة : المنهج الوصفي الأدوات المستخدمة في الدراسة الإستبيان الكلمات المفتاحية بالعربية: التمكين الإداري، التميز، المركبات الرياضية. الكلمات المفتاحية بالإنجليزية Keywords : Management empowerment, excellence, sports vehicles. جاء هذا البحث في فصول . الفصل الأول: الإطار العام للدراسة وتناول الفصل الثاني: التمكين الإداري: أما الفصل الثالث التميزذ بالمركبات الرياضية: الفصل الرابع: الدراسة التطبيقية من أهم النتائج التي توصل إليها الباحث : : *تطبيق المفاهيم الإدارية الحديثة لدى إدارة المؤسسات الرياضية مثل تفعيل مبدأ المشاركة العمل والعمل الجماعي وصنع القرار الإداري بما يشجع الإبداع لدى العاملين. * تهيئة بيئة العمل بمديرية الشباب والرياضة بما يدعم التمكين، من خلال تبني التعاون * العمل على إتباع اللامركزية ومشاركة المرؤوسين في إتخاذ القرارات. * العمل على إنشاء إدارة حاضنة للإبداع حيث تكون مسؤولة عن دعم وتشجيع المبدعين والمتميزين أهم التوصيات لابد من زيادة سرعة وسهولة انسياب المعلومات حيث أنها عامل مهم جداً ضرورة العمل على تعزيز التمكين في المؤسسات الرياضية، وكذلك تشجيع العاملين لتقديم المبادرات خارج التعليمات الرسمية، وكذلك إتاحة المزيد من هامش الحرية للعاملين في تحديد الأسلوب الأنسب لإنجاز الأعمال. _لابد على المسؤولين رفع ثقة المرؤوسين في قدراتهم ومهاراتهم إذ إنها أحد المقومات الأساسية لنجاح تطبيق مفهوم التمكين وتحقيق التميز في المؤسسات الرياضية. Searchlight in English Faculty Institute of Sciences and Sports and Technical and Physical Activities Department: Order No: No. d 'registration : 23064097928 Searcher : RAHMANI Abdelaziz Publicly supported on. 21-6-2024 Title of the thesis (dissertation): The role of administrative empowerment in achieving excellence in sports vehicles. A field study of the neighborhood sports complex, Rawahi Rabeh, in Hammam Al-Dalaa. Language of the thesis: Arabic. Model of the thesis Country: REPUBLIC OF ALGERIA-M'SILA University: University of M'sila Surname and first name of the supervisor : karrouche nouari Grade: Master Lecturer Number of pages:109 Option:. Summary: This study aims to introduce the subject of the role of administrative empowerment in achieving excellence in sports vehicles with a case study of the sports complex Al-Jawari Rawabahi Rabeh in Hammam Al- Dhala at his time The study was divided into 3 aspects, a methodological aspect, a theoretical side and an applied aspect, in addition to the use of the questionnaire as a main tool in collecting data and information, which was analyzed based on the statistical package program spss, as well as the study relied on the descriptive analytical approach, and we have reached a set of results, the most important of which are: - Demonstrate that communication and information sharing play a role in achieving excellence in sports vehicles. - Proving that trust between employees and officials has a role in achieving excellence in sports vehicles. - Proving that material and moral incentives have a role in achieving excellence in sports vehicles. Title of the study:, The role of administrative empowerment in achieving excellence in sports vehicles. A field study of the neighborhood sports complex, Rawahi Rabeh, in Hammam Al-Dalaa. The purpose of the study: . The concept of administrative empowerment, its components and importance, and the concept of the performance of employees in sports vehicles - Through the theoretical framework. - *Highlighting the role of implementing the administrative empowerment policy in achieving excellence in sports vehicles.  *Recognizing the basic elements of administrative empowerment (communication, information sharing, and trust among employees  Officials and material and moral incentives) and their role in achieving excellence within sports vehicles.  *The possibility of arriving at conclusions by analyzing the answers of the study sample and the importance of applying administrative empowerment Problem Does administrative empowerment play a role in achieving excellence in sports vehicles? Hypotheses: Administrative empowerment has a role in achieving excellence in sports vehiclesCommunication and information sharing play a role in achieving excellence in sports vehicles.  Trust between employees and officials plays a role in achieving excellence in sports vehicles.  Material and moral motivation play a role in achieving excellence in sports vehicles. Key words : Management empowerment, excellence, sports vehicles - The most important results achieved are: Applying modern administrative concepts in the management of sports institutions, such as activating the principle of participation Work, teamwork, and administrative decision-making to encourage creativity among employees. * Preparing the work environment in the Youth and Sports Directorate to support empowerment, by adopting cooperation * Working to follow decentralization and the participation of subordinates in decision-making. * Working to establish an incubator department for creativity that will be responsible for supporting and encouraging creative and distinguished people
Keywords: التمكين الإداري; التميز; المركبات الرياضية